Proximate Quality of Low-Sodium Salted Egg - Hajar Setyaji; Metha Monica (Postgraduate, University of Mataram, 2023)
This study aims to determine the use of low-sodium salt for the proximate quality of salted eggs. The research method used a complete randomized design with P0 control treatment, 10% P1 low sodium salt treatment, 20% P2 low sodium salt treatment, and 30% P3 low sodium salt treatment. Analysis data was carried out on the contents of water, protein, lipid, and ash content. The data were analyzed using SPSS with a significance level of 0.05. The results indicated that the water content of egg whites and egg yolks was not significantly different from the treatment of ordinary salt and low sodium salt treatment. The lipid content was also not significantly different at all treatments. Protein content, ordinary salt treatment, and low sodium salt provided a noticeable difference in egg white protein content (p<0.05). Making salted eggs using low-sodium salt produces salted eggs with the similar proximate quality as the control with the lower sodium levels than the control treatment.